2021
DOI: 10.2147/cmar.s240600
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Management of Anemia in Patients with Myelodysplastic Syndromes: An Update on Emerging Therapeutic Options

Abstract: For the majority of patients with lower-risk myelodysplastic syndrome (LR-MDS), one of the primary clinical goals is to alleviate the symptoms associated with the resultant cytopenias and to minimize the transfusion burden. While supportive red blood cell (RBC) transfusions and erythropoiesis-stimulating agents (ESAs) may lead to clinical improvement, frequent transfusions are often complicated by iron overload and decreased quality of life; furthermore, most patients either do not respond to ESAs or will even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 120 publications
0
7
0
Order By: Relevance
“…ESA-resistant patients could be treated with the standard roxadustat 1.5 mg/kg dose without increasing dose size or frequency, as required with darbepoetin [ 4 ]. First results indicate that anemia due to myelodysplastic syndrome also responds to usual doses of roxadustat with prolonged transfusion independence [ 41 ].…”
Section: Clinical Efficacymentioning
confidence: 99%
“…ESA-resistant patients could be treated with the standard roxadustat 1.5 mg/kg dose without increasing dose size or frequency, as required with darbepoetin [ 4 ]. First results indicate that anemia due to myelodysplastic syndrome also responds to usual doses of roxadustat with prolonged transfusion independence [ 41 ].…”
Section: Clinical Efficacymentioning
confidence: 99%
“…Preclinical studies have shown that the antineoplastic effects of lenalidomide include direct antineoplastic activity, immunologic effects mediated by inhibition of tumor cell proliferation and angiogenesis, and stimulation of cytotoxicity mediated by T cells and NK cells [ 4 7 ]. Moreover, its activity has been demonstrated in a wide spectrum of hematologic malignancies, including myelodysplastic syndromes [ 8 ], multiple myeloma [ 9 , 10 ], and B-cell NHL [ 11 ]. Several clinical trials have shown that lenalidomide has efficacy against DLBCL and is well tolerated, and it is expected to become a new treatment option for DLBCL [ 12 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hypoxia-inducible factor-proline hydroxylase inhibitors (HIF-PHI) as a novel class of therapeutic agents have been developed to treat anemia in CKD patients. HIF is a key transcription factor primarily involved in the cellular regulation and efficiency of oxygen delivery . Roxadustat ( 1 ) (FG-4592) (Figure ) developed by FibroGen is the first HIF-PHI, which was already approved as Ai Rui Zhuo in China and Evrenzo in Japan. , It is administered orally, which is a major advantage over drugs for parenteral use only, and it is used to treat anemia in CKD patients on dialysis and not on dialysis as well as in myelodysplastic syndromes . FibroGen company has submitted an application to the Food and Drug Administration (FDA) for permission to use roxadustat ( 1 ) in patients with chronic renal failure accompanied by anemia.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 It is administered orally, which is a major advantage over drugs for parenteral use only, and it is used to treat anemia in CKD patients on dialysis and not on dialysis 11−13 as well as in myelodysplastic syndromes. 14 FibroGen company has submitted an application to the Food and Drug Administration (FDA) for permission to use roxadustat (1) in patients with chronic renal failure accompanied by anemia. The application is under consideration to date.…”
Section: ■ Introductionmentioning
confidence: 99%